Evaluation of master swimmers health: the case of French National Championships - Potdevin, F.; Vanlerberghe, G.; Zuinquin, G.; Pezze, T.; Theuninck, D. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Among physical activity exercises, swimming is often recommended to increase physical activity and gain health benefits by various authoritative groups and researchers (European society of hypertension, 2003). According to World Health Organization, the health concept has to be defined as `a complete state of mental, physical and social well being` and considered as `a resource for every day life` suggesting a multi-physical-psychological and social parameters analyses in order to study health benefits. `Competitive master swimmers` appeared to be interesting subjects in the study of health benefits by swimming because they spend more time training in comparison with the average sedentary person and allowed a long term effect of this practice. The aim of this study was therefore to assess global health benefits of practice swimming in master population involved in a national level of practice.